The effectiveness of air and gas-air tamponade in the surgical treatment of retinal detachment associated with inferior breaks - A. V. Mironov; F. T. Murtazalieva; I. M. Kutin (Российский офтальмологический журнал, 2025)
Retinal detachment (RD) is a severe ophthalmologic disease that requires urgent surgical intervention. However, the choice of a tamponade agent for filling the vitreous cavity after surgery has been debatable to date. Purpose of the study was to evaluate the efficacy of air and gas-air tamponade of the vitreous cavity in surgical treatment of RD with tears in the inferior quadrants of the fundus. Material and methods. The study included 21 patients with primary rhegmatogenous RD caused by peripheral tear flaps in the inferior quadrants. A study was conducted of 21 patients with primary rhegmatogenous retinal detachment, the cause of which was peripheral breaks in the lower quadrants. The patients were divided into 2 groups depending on the type of vitreous cavity tamponade. In group 1 (10 patients), the best corrected visual acuity (BCVA) before surgery was 0.01–0.7 (±0.04). The surgery was completed by tamponade of the vitreous cavity with a gas-air mixture of sulfur hexafluoride (SF6). In the 2nd group (11 patients), the preoperative BCVA was 0.01–0.8 (±0.07). Surgical treatment in patients of this group was completed with tamponade of the vitreous cavity with sterile air. Results. In the early postoperative period, reactive ophthalmic hypertension was observed in patients of the 1st group, intraocular pressure in the 2nd group was within normal limits. After 6 months, according to B-scan data, the membranes were adjacent in both groups, and no recurrence of RD was registered. BCVA was 0.5–1.0 (±0.04) and 0.6–1.0 (±0.046) in the 1st and 2nd groups, respectively. Conclusion. Considering comparable anatomical, functional and clinical postoperative results, the use of air tamponade of the vitreous cavity is the preferred method in the surgical treatment of rhegmatogenous RD associated with inferior tears.